Protective Effect of Peptide Calcium Channel Blocker Omega-Hexatoxin-Hv1a on Epithelial Cell during Ischemia-Reperfusion Injury - Elena Iurova; Eugenia Rastorgueva; Evgenii Beloborodov; Evgeniya Pogodina; Aleksandr Fomin; Dmitrii Sugak; Denis Viktorov; Ivan Tumozov; Yury Saenko (MDPI AG, 2023)
Ischemia-reperfusion injury (IRI) is a common phenomenon that develops both from natural causes and during major operations. Many intracellular processes mediated by calcium ions are involved in the development of IRI. Currently, chemical calcium channel blockers are used but they have a number of limitations. In this article, we study the effect of the omega-hexatoxin-Hv1a peptide toxin, an alternative to chemical calcium channel blockers, on the mechanisms of IRI development in epithelial cell culture. The toxin was produced using solid phase peptide synthesis. IRI was caused by deprivation of glucose, serum and oxygen. The data obtained demonstrate that the omega-hexatoxin-Hv1a toxin in nanomolar concentrations is able to prevent the development of apoptosis and necrosis in epithelial cells by reducing the concentration of calcium, sodium and potassium ions, as well as by delaying rapid normalization of the pH level, affecting the mitochondrial potential and oxidative stress. This toxin can be used as an alternative to chemical calcium channel blockers for preventing tissue and organ IRI due to its low-dose requirement and high bioavailability.